Study on Influencing Factors of Roadway Surrounding Rock Stability of Extremely Weak Coal Seam In Wangxingzhuang Coal Mine - Chi, Pan (International Journal of Natural Resources and Environmental Studies, 2025)
The Er1 coal seam in Wangxingzhuang Coal Mine is an extremely weak coal seam. In order to explore the influence degree of geological conditions such as tunnel burial depth, seam thickness, mining influence, and support parameters such as bolt cable row spacing and U-shaped steel row spacing on the stability of roadway surrounding rock, this paper adopts the orthogonal test design numerical simulation scheme and evaluates the influence degree of each factor on the test index through range analysis. The results provide the parameter basis for roadway support of extremely weak coal seam in Wangxingzhuang Coal Mine. The research results of this paper have certain theoretical significance and engineering practice value.